Harness and implements for animal power - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Harnessing and implements for animal traction: an animal traction resource book for Africa by Paul Starkey 1989, 245 pp ISBN 3 528 2053 9 'Animal traction resource books'